Double beta decays into excited states in 110Pd and 102Pd. (17th October 2016) - Lehnert, B; Andreotti, E; Degering, D; Hult, M; Laubenstein, M; Wester, T; Zuber, K
Abstract: A search for double beta decays of 110 Pd and 102 Pd into excited states of the daughter nuclides has been performed using three ultra-low background gamma-spectrometry measurements in the Felsenkeller laboratory, Germany, the HADES laboratory, Belgium and at the LNGS, Italy. The combined Bayesian analysis of the three measurements sets improved half-life limits for the 2 νββ and 0 νββ decay modes of the 2 1 +, 0 1 + and 2 2 + transitions in 110 Pd to 2.9 · 10 20 yr, 4.0 · 10 20 yr and 3.0 · 10 20 yr, respectively, and in 102 Pd to 7.6 · 10 18 yr, 8.8 · 10 18 yr and 1.4 · 10 19 yr, respectively, with 90% credibility.